A narrativa imagética e sonora em Amorteamo (2015) - Souza, Carla Patrícia Oliveira de (2020)
This research proposes to study serial television fictions, especially those that contain fantastic elements in their narrative. Thus, we selected the miniseries Amorteamo (2015), directed by Flávia Lacerda and broadcast by the Rede Globo de Televisão, as our object of study. This miniseries was freely inspired by the work Assombrações do Recife Velho (2008), by Gilberto Freyre, and by other sources, such as the stop motion film Corpse bride (2005), by Tim Burton. We reflected on Amorteamo from the main elements that make up this supernatural narrative set in the Brazilian northeast: the traditional legend and its circulation in contemporary times, melodrama and fantastic literature are addressed, as well as the aesthetics and musicality of the scenes. The German expressionism is the visual concept worked on in the work, represented in the deformed and worn out scenarios and also in the characters' costumes. The sound is praised in the audiovisual work through the musicized scenes, that is why we establish an understanding of the present interplay between the expressionist images and the sound of Amorteamo. In order to carry out such an interpretation, we seek the semiotics of culture of Russian origin, represented by the linguist Iúri Lótman (1996) and by the Brazilian researcher Irene Machado (2003), since this theory provides us with categories of analysis that allow us to discuss all the present symbology in the images and sounds of the miniseries. The thesis that will guide the research in Amorteamo seeks to think about the construction of meanings that exude from semiotic systems of culture in the image and sound narrative, especially those that dialogue with the life and death dichotomy. In our interpretative path, added to the authors already cited, we mainly use the theoretical contributions of semioticians Ramos (2007), Américo (2017), in addition to Todorov (2006), Propp (1984), Greimas (1973), Eisner (1985), Lira (2013), Chion (2016), Rodriguez (2006), Lurie (1997) and Leite e Guerra (2002).